Capacity assessment of eco-labelling implementation: the case of the vietnam green label program - Truong Thi Ai Nhi; Vilas Nitivattananon; Kim, Sohee Minsun; Swierczek, F.W.; AITCV Silver Anniversary Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Eco-Labels (ELs) have become a practical strategy to promote the green consurnption all over the world and be a critical part to fill in the gap in the balance of sustainable consumption and production, one of the Sustainable Development Goals. However, very few researches have been conducted to systematically understand the capacity, particularly in developing countries, in implementing ELs through a systematic process of assessment towards capacity development. This research mainly aims to assess the current capacity of Vietnam Green (VOL) Program through the flow of capacity assessment of stock-taking through thematic and cross-cutting capacity assessment with inputs from relevant stakeholders to point out the key factors of the program success. Both qualitative method on identifying internal and external motivations and challenges, as well as strengthening strategies and quantitative r:nethod to determine the priorities in were used and constructed this study. Secondary data through literature review and primary data by thirty-two respondents' evaluations are consistently combined to support the methods. The study has found that there is still limited capacity in VOL implementation. Despite the compromising conditions for the implementation and development, its performance is still unsatisfactory with low quantity and quality of outcomes, lack of consumer-based approach, shortage of stakeholders' participation and integration with sustainable public procurement. Based on the evaluation, VLG is also observed with lower level of practices in which finance and incentive are rated as the worst practices. Although VOL capacity concerns are mostly related to management issues, utilizing the opportunities to push VGL's development should be prioritized, rather than fixing the management issues. Prioritized strategic actions which require further policy development are proposed, such as consumer based approach through consumption behavior change and market driven toward green products. They not only create output for the green products but also consequently promote the implementation of the program. Within this study, a framework and a concept of capacity assessment on a national program by multi-stakeholders are developed which can be further applied while the results on VOL capacity assessment and strengthening strategies can be adopted by other EL schemes. A new approach of Analytic Hierarchy Process application in capacity assessment has also been introduced in order to achieve the objective results which are based on the harmonized inputs.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M. Sc.) - Asian Institute of Technology, 2017
Keywords: Algorithms; Decision making -- Mathematical models